Geomorphic Site Analysis to Study Soils Developed on a Toposequence of Schist Landform in Yadgir District of Karnataka - Anil R. Chinchmalatpure, Veeresh1, H.V. Rudramurthy, K. Basavaraj and (Journal of the Indian Society of Soil Science, 2016)
Three representative diversified pedons namely red, brown and black from the geomorphic units upper, middle and lower sectors, respectively in a toposequence on schist landscape were studied for their morphological, physical and chemical properties to understand the genesis and to classify as per USDA Soil Taxonomy. Red pedon was well drained as it recorded the highest (3) moist chroma and the drainage got poor down the slope in brown and black pedons where the moist chroma was 2 and 1, respectively. Dominant soil colour hue was 5YR in red pedon and 7.5 YR and 10 YR in brown and black pedons, respectively. Soil texture got finer down the slope and it was gravelly clay loam in red pedon and clay in both brown and black pedons. Clay skins, pressure faces and slickensides were observed in red, brown and black pedons, respectively. Chemical composition of fine sand fraction of pedons was almost same in all the pedons and CEC/clay, Feo/Fed and SiO2/Fe2O3 ratios showed increasing trend down the slope. The pedogenic processes associated with the upper sector member red pedon were leaching, decalcification, tendency of desilicification, laterization and kaolinization under well drained condition whereas, the middle and lower sector members brown and black pedons were formed by the pedogenic processes like calcification and silicification under poor drainage condition. Thus, a difference in drainage conditioned by topography is the important pedogenic factor in the genesis of diversified soils in a toposequence. At sub group level red, brown and black pedons were classified as Typic Haplustalfs, Vertic Haplustepts and Leptic Haplusterts, respectively.